Analisis daya terima bakso ikan tenggiri dan daun kelor (Scomberomorus Commerson & Moringa Oleifera) sebagai pangan lokal bergizi pada balita stunting usia 36-59 bulan - Erna Amalya; Nur Husnul Khatimah; Dea Zara Avila; Alkhair Alkhair (Holistik Jurnal Kesehatan, 2026)
Background: Stunting remains a major nutritional problem in Indonesia and can affect children's growth and development. Utilizing nutrient-rich local foods is one strategy to support nutritional improvement in stunted children. Spanish mackerel (Scomberomorus commerson) is a good source of high-quality animal protein, while moringa leaves (Moringa oleifera) are rich in vitamins, minerals, and antioxidants. These ingredients have the potential to be developed into nutritious food products. However, consumer acceptance is a critical factor determining product utilization. Purpose: To analyze the acceptability and differences in sensory evaluation of mackerel meatballs enriched with moringa leaves in stunted children aged 36–59 months. Method: This experimental study used three formulations of Spanish mackerel meatballs with different concentrations of moringa leaves: F1 (10%), F2 (15%), and F3 (20%). The study was conducted in June 2025 within the working area of ​​the Langgudu Timur Community Health Center, Bima Regency, West Nusa Tenggara. Acceptability testing was conducted by 30 panelists using a hedonic test covering aspects of taste, color, aroma, and texture on a five-point scale. Data were analyzed using the Friedman test at a 95% confidence level (α=0.05). Results: Significant differences in acceptability were found among the three formulations for all sensory aspects (p<0.05). Formulation F2 had the highest average ratings for taste (2.53), aroma (2.60), and texture (2.82). Meanwhile, formulation F3 had the highest average rating for color (2.82). Overall, formulation F2 demonstrated the highest level of acceptability among panelists. Conclusion: There were significant differences in acceptability of mackerel fish balls with added moringa leaves based on taste, color, aroma, and texture. Formulation F2, containing 15% moringa leaves, was the most preferred formulation and has the potential to be developed as a nutritious local food alternative to support stunting prevention and management programs. Suggestion: Further research is recommended to analyze the nutritional content, product shelf life, and examine the effect of mackerel fish ball and moringa leaf consumption on the nutritional status and growth of stunted children to gain a more comprehensive understanding of the product's benefits.   Keywords: Acceptability; Moringa Leaves; Local Nutritious Food; Spanish Mackerel Meatballs; Stunting.